Tenofovir disoproxil fumarate therapy to prevent hepatitis B virus vertical transmission—A review of maternal and infant outcomes. (31st March 2022) - Samadi Kochaksaraei, Golasa; Shaheen, Abdel A.; Seow, Cynthia H.; Barkema, Herman W.; Coffin, Carla S.
Abstract: Hepatitis B virus (HBV) is a global health problem. Vertical transmission of HBV from HBV surface antigen (HBsAg)‐positive mothers to their infants is the most common cause of HBV infection worldwide. The use of passive–active immunoprophylaxis is >90% effective in reducing the risk of vertical transmission, but immunoprophylaxis failure can occur in infants born to mothers with high viraemia. Thus, it is recommended that pregnant women with HBV‐DNA level >200 000 IU/ml receive nucleos(t)ide analogue (NA) treatment [i.e. tenofovir disoproxil fumarate (TDF), lamivudine or telbivudine] during third trimester to prevent infant immunoprophylaxis failure. TDF is recommended as the first‐line therapy based on available data on efficacy, safety and resistance profile. However, maternal immunological reconstitution following parturition can increase immune‐mediated flares to viral antigens that is potentially exacerbated following TDF withdrawal. In this article, we review available data on the efficacy and safety of TDF administration to prevent HBV mother‐to‐child transmission. We also discuss changes in maternal viral markers [i.e. HBV‐DNA, HBV e antigen and HBsAg] and alanine aminotransferase during follow‐up post‐partum in mothers received NA to prevent HBV vertical transmission.